Lower limb muscles activation of endurance and power athletes - Sulaiman, M.; Azaman, A.; Salleh, M. A.; Yahya, A. (IFMBE Proceedings, 2021)
Abstract: Power and endurance athletes have different physiological and metabolic properties of their skeletal muscle. The aim of this study was to compare the muscle activation between these two types of athletes by evaluating the muscle perfomance accessed from various types of lower limb muscles. A total of 27 subjects; 14 power athletes, and 13 endurance athletes voluntarily participated in this study. Electromyographic (EMG) signals were recorded from five lower limb muscles; vastus lateralis, rectus femoris, tibialis anterior, gastrocnemius and soleus muscle of dominant leg using wireless electromyography system. EMG signals were analysed by extracting several time and frequency domain features in order to evaluate the contribution of each muscles in distinguishing between power and endurance athletes. Comparison between groups was quantified and evaluated by Mann-Whitney U Test. Result showed that significant difference (p < 0.05) was found only in vastus lateralis, rectus femoris and tibialis anterior muscle for several EMG features. Meanwhile, no group differences were observed for gastrocnemius and soleus muscle in all features. Finding shows that physiological differences between power and endurance athletes was much easier to be accessed from vastus lateralis muscle as indicated by significant test result of most selected EMG features.